Three new species of the genus Clubiona from China (Araneae: Clubionidae) - Liu, Ping; Yan, Heng-Mei; Griswold, Charles; Ubick, Darrell (Zootaxa, 2007)
The present paper deals with three new species of the genus Clubiona collected from the Gaoligong Mountains Region of Yunnan Province, China: Clubiona applanata sp. nov., Clubiona altissimoides sp. nov., Clubiona cylindrata sp. nov.